2000
DOI: 10.1088/0031-9155/45/3/307
|View full text |Cite
|
Sign up to set email alerts
|

Experimental kerma coefficients and dose distributions of C, N, O, Mg, Al, Si, Fe, Zr, A-150 plastic, Al2O3, AlN, SiO2and ZrO2for neutron energies up to 66 MeV

Abstract: Low-pressure proportional counters (LPPCs) with walls made from the elements C, Mg, Al, Si, Fe and Zr and from the chemical compounds A-150 plastic, AlN, Al2O3, SiO2 and ZrO2 were used to measure neutron fluence-to-kerma conversion coefficients at energies up to 66 MeV. The LPPCs served to measure the absorbed dose deposited in the gas of a cavity surrounded by the counter walls that could be converted to the absorbed dose to the wall on the basis of the Bragg-Gray cavity theory. Numerically the absorbed doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…3. The experimental data (full square) [17] [18] are derived from different oxides, and the residual data (full dot) [13] are measured by Meulders et al Using the elastic cross sections and the 1st Legendre coefficients of ENDF/B-VIIb.3, we can reproduce the structural curves of the elastic recoil kerma coefficients below 30 MeV and the total kerma coefficients in the lower energy region. However, the present work underestimates the total kerma coefficients at about 6-20 MeV neutron region, and overestimates them above 20 MeV.…”
Section: Calculation Resultsmentioning
confidence: 99%
“…3. The experimental data (full square) [17] [18] are derived from different oxides, and the residual data (full dot) [13] are measured by Meulders et al Using the elastic cross sections and the 1st Legendre coefficients of ENDF/B-VIIb.3, we can reproduce the structural curves of the elastic recoil kerma coefficients below 30 MeV and the total kerma coefficients in the lower energy region. However, the present work underestimates the total kerma coefficients at about 6-20 MeV neutron region, and overestimates them above 20 MeV.…”
Section: Calculation Resultsmentioning
confidence: 99%
“…[35], and the other experimental data (open squares, full dots) are derived from Refs. [2,4], respectively. The evaluated results of Ref.…”
Section: Total Kerma Coefficientsmentioning
confidence: 99%
“…The three Schrewe experimental data sets (see legend) are derived from different oxides in Ref. [2], and the residual data (full dots) are from Ref. [4].…”
Section: Total Kerma Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron kerma coefficients, absorbed dose and dose equivalent data are important in radiation protection and therapy. For neutron kerma coefficients, several calculations (Caswell et al 1980, Alekseev et al 1986, Slypen et al 2000 and numerous measurements (DeLuca et al 1984, Menzel et al 1984, Wuu and Milavickas 1987, McDonald and Cummings 1988, Hartmann et al 1992, Benck et al 1998, Schrewe et al 2000, Bergenwall et al 2004 have been reported. A problem is that, due to the lack of precise experimental cross section data and different treatments for high-energy neutron interaction with light nuclei and compounds, marked discrepancies have appeared between various results for kerma coefficients.…”
Section: Introductionmentioning
confidence: 99%